Landowner Cooperative Key to Success in the Bee Ridge Quail Focus Area - John A. Pinkowski; Beth A. Emmerich; William T. White (National Quail Symposium Proceedings, 2022)
The Missouri Department of Conservation (MDC) began establishing Quail Focus Areas (QFAs) on private lands in 2004. The goal of QFAs is to increase and expand quail habitat management efforts around a core area. Because most (93%) of the landscape of Missouri, USA is in private ownership, habitat improvement programs on private lands have greater potential to impact quail populations than on public lands alone. A motivated group of landowners led the charge to begin habitat improvement efforts in the Bee Ridge QFA. This group was instrumental in starting earlier monitoring efforts to determine whether habitat improvements were leading to increased northern bobwhite (Colinus virginianus; hereafter, bobwhite) numbers. In fall 2017, MDC staff began monitoring bobwhite and songbirds in a portion of the Bee Ridge QFA in Knox County, Missouri and in a control area (without habitat management for bobwhite). This effort is part of the Coordinated Implementation Plan developed by the National Bobwhite Technical Committee as a part of the National Bobwhite Conservation Initiative. The goal of the monitoring plan is to document whether quail habitat management can achieve sustainable bobwhite populations within 5–10 years. We selected a 2,225-ha portion of the Bee Ridge QFA where habitat management for quail has been conducted through efforts by landowners and MDC staff. Point transect surveys are conducted at 46 250-m radius points in spring for bobwhite and songbirds and at 12 500-m radius points in fall for bobwhite coveys. Bobwhite densities ranged from 0.23 bobwhite/ha (95% credible interval [CrI] = 0.14–0.35) to 0.27 bobwhite/ha (95% CrI = 0.15–0.43) in the focus area and 0.03 bobwhite/ha (95% CrI = 0.01–0.08) to 0.06 bobwhite/ha (95% CrI = 0.01–0.15) in the control area from 2013 through 2019. Landowners working together to implement recommended habitat management practices resulted in greater quail and songbird numbers in the focus area, compared to the control area.
Keywords: Colinus virginianus; point transet surveys; focus area; monitoring; private land; Missouri; northern bobwhite